Formation of the Company’s Competitive Advantages in the Supply Chain Management and Digital Economy - Roman Nikulin; Nailya Bagautdinova (International Journal of Supply Chain Management, 2019)
The article reveals basic competitiveness elements of modern enterprises in the digital economy and its effects on the supply chain strategy. Currently, the search for new sources of competitiveness focuses not only on the field of scientific, technological and innovation policies of the enterprise, but also on the Internet space, which forms new digital formats of intra-and inter-process interaction. The authors emphasize the basic elements of competitiveness in the digital economy: virtual ecosystems, platform enterprises, digital resources, Smart management. The article presents various approaches to the concept of